The Trouble with Peace: The Royal Army Medical Corps' Cold War Recruitment Conundrums. (3rd April 2018) - Fitzpatrick, Meghan
Abstract : This article examines the Royal Army Medical Corps' (RAMC) recruitment problems throughout the Cold War (1945–1980s). It explores why the RAMC experienced difficulties in attracting new personnel, how the army tried to alleviate these shortages, and the impact of chronic understaffing on the quality of military health care for generations of soldiers and their families. It concludes by reflecting on the enduring dilemmas of recruiting professionals in peacetime.